2006
DOI: 10.1079/pns2005484
|View full text |Cite
|
Sign up to set email alerts
|

Maternal nutrient restriction alters renal development and blood pressure regulation of the offspring

Abstract: Studies have shown that the risk of hypertension in adulthood can be affected by the in utero environment. It is established that hypertension is linked to compromised kidney function and that factors affecting organogenesis can increase the risk of later disease. Prostaglandins (PG) and growth factors are known to play an important role in regulating kidney function and renal organogenesis. The extent, however, to which global energy restriction (where all nutrients are reduced) of the mother can programme la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 79 publications
(101 reference statements)
2
28
0
1
Order By: Relevance
“…In association with their smaller size in the newborn period, the kidneys of the NR animals had significantly fewer nephrons from 7 days after birth to adulthood but not at birth, which was coincident with the time at which plasma corticosterone remained at the relatively high postpartum concentrations in NR offspring, rather than falling as in controls (2). Interestingly, a similar magnitude of maternal nutrient restriction but commencing on day 13 of gestation in Wistar rats led to elevated fetal plasma corticosterone levels on day 21 of gestation and lower placental levels of 11ā¤-hydroxysteroid dehydrogenase type 2 mRNA (16).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In association with their smaller size in the newborn period, the kidneys of the NR animals had significantly fewer nephrons from 7 days after birth to adulthood but not at birth, which was coincident with the time at which plasma corticosterone remained at the relatively high postpartum concentrations in NR offspring, rather than falling as in controls (2). Interestingly, a similar magnitude of maternal nutrient restriction but commencing on day 13 of gestation in Wistar rats led to elevated fetal plasma corticosterone levels on day 21 of gestation and lower placental levels of 11ā¤-hydroxysteroid dehydrogenase type 2 mRNA (16).…”
Section: Discussionmentioning
confidence: 98%
“…At day 14, higher plasma corticosterone in postnatal NR offspring was observed (2). It is established that nephrogenesis in the fetal rat begins at 12 days of gestation and is largely complete by postnatal day 14 (35), so elevated plasma corticosterone would only inhibit this process if this occurred before this date.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Different perturbations in the feto-maternal environment, such as a low-protein maternal diet and placental insufficiency, have been known to alter kidney weight and glomerular number and size. 25,26 Because a final wave of nephrogenesis is observed during the first week of life in the mouse, 27 kidney formation and protein activation were examined at postnatal days 17 and 21.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Festing recommended researchers use the number of dams in developmental animal studies [19]; however, we have found significant changes of phenotype in offspring with similar animal studies in comparison based on numbers of pups [8,9,11]. We therefore used the number of pups, not dams, as the basic unit that maternal caloric restriction during pregnancy can predispose adult offspring to increased blood pressure [4], dysglycemia [5], dyslipidemia [6], and obesity [7], which correspond to cVd risk factors in humans concomitant with individual genetic and environmental backgrounds. Recently we reported a mouse animal model of maternal caloric restriction during the later half of pregnancy (30% reduction vs ad libitum feeding) where offspring developed an obesity-prone phenotype when given a high-fat diet in adulthood due partly to permanently low hypothalamic leptin sensitivity [8,9]; these findings support the concept of developmental origins of obesity in humans [10].…”
Section: Mouse Model Of In Utero Undernutritionmentioning
confidence: 99%